2010
DOI: 10.1002/chem.201002415
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Organocatalytic Formal Aza‐Michael Addition of Ammonia to Nitroalkenes

Abstract: The formal addition of ammonia to nitroalkenes, affording optically active β‐amino nitro compounds in high yields and enantioselectivities, is presented (see scheme). The approach is based on a novel thiourea‐catalyzed aza‐Michael reaction, by which benzophenone imine serves as a masked ammonia equivalent, which is released by hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Next, thiourea 28 is known to activate nitro-olefins for the aza-Michael addition of imines ( eq 11). 34 Indeed, thiourea 28 also induces the [4+2] cycloaddition although the yield and ee are low (eq 12), implicating that a stepwise mechanism is feasible. In addition, we treated imine 29 with nitro-alkene 19 in the presence of the Zn•F-BOPA catalyst and found that the aza-Michael adduct is formed in excellent yield (eq 13).…”
Section: Resultsmentioning
confidence: 99%
“…Next, thiourea 28 is known to activate nitro-olefins for the aza-Michael addition of imines ( eq 11). 34 Indeed, thiourea 28 also induces the [4+2] cycloaddition although the yield and ee are low (eq 12), implicating that a stepwise mechanism is feasible. In addition, we treated imine 29 with nitro-alkene 19 in the presence of the Zn•F-BOPA catalyst and found that the aza-Michael adduct is formed in excellent yield (eq 13).…”
Section: Resultsmentioning
confidence: 99%
“…[5] Jørgensen and co-workers reported the use of 1,2,4-triazoles as good amine surrogates for secondary-amine-catalyzed enantioselective aza-Michael reactions with a,b-unsaturated aldehydes. ] and imines [15] have also been reported as valid nitrogen sources for asymmetric aza-Michael reactions under iminium catalysis.Ooi and co-workers reported au nique arylaminophosphonium-catalyzed asymmetric addition of 2,4-dimethoxyanilines to nitroolefins. [16] Theonly reaction of this type involving abasic amine was reported by Sundararajan and Prabagaran, who used ap olymer-supported Lewis acid as the catalyst and found that benzyl amine reacted with ethyl cinnamate to give the product with 81 % ee.…”
mentioning
confidence: 99%
“…A facile and efficient asymmetric organocatalytic formal amination of nitroalkenes 52 that gives access to enantioenriched primary amines was developed by Jørgensen et al by utilizing benzophenone imine 53, produced by condensation of benzophenone and ammonia, as an ammonia equivalent (Scheme 12). [18] This process, which is catalyzed by a Jacobsentype thiourea catalyst 54, furnished the aza-Michael adducts 55 in 79-95 % yield and 78-92 % ee. A one-pot asymmetric aza-Michael addition-acidic hydrolysis protocol was also developed and the hydrochloride salt of the primary b-amino nitro compounds 56 were obtained in good yields (60-80 %, 2 steps) and enantioselectivities (78-84 % ee) consistent with the results obtained for the adducts 55.…”
Section: Intermolecular Aza-michael Additionsmentioning
confidence: 99%